The role of situational variables in analysing physical performance in soccer - Lago-Penas, C. (Journal of Human Kinetics, 2012)
erformance analysis in sport is used to investigate the performance of teams and players across different sports. Research within this area, especially when focussing on the determinants of success, has grown rapidly in the last few years. During this time, the role of a new concept, `situational variables` has emerged. This term includes the different game and situational conditions that may influence performance at a behavioural level. Given that soccer is dominated by strategic factors, it is reasonable to suggest that situational variables of match status (i.e. whether the team is winning, losing or drawing), quality of opposition (strong or weak), and match location (i.e. playing at home or away) may somehow influence the teams´ and players´ activities. These situational variables need to be analyzed in depth to understand their influence in team sports. The aim of this article was to examine the independent and interactive effects of situational variables on physical performance in elite soccer. The view that professional soccer players regulate their physical efforts according to the specific demands of individual matches and periods of the game is offered. In support of this argument results from recent studies are presented. Implications of this perspective for match analyst and coaches for evaluating performance are also considered.